Implementation of The Integrated Islamic School Network Curriculum at SMP IT Darul Hasan Padangsidimpuan - Sormin, Darliana; Salamah, Nurani; Pasaribu, Muksana; Rahmayanti Sormin, Mira (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The curriculum serves as the foundation for the implementation of learning in integrated Islamic schools under the auspices of JSIT. Darul Hasan Integrated Islamic Junior High School (SMP Islam Terpadu Darul Hasan) in Padangsidimpuan is one of the integrated Islamic educational institutions under JSIT. Accordingly, Darul Hasan Integrated Islamic Junior High School implements the JSIT curriculum. The purpose of this research is to describe how the JSIT curriculum is implemented at Darul Hasan Integrated Islamic Junior High School in Padangsidimpuan and to identify any obstacles in its implementation. The research methodology used in this study is a qualitative research method, involving observations and structured interviews with research informants as data collection techniques. The results of this study conclude that the implementation of the JSIT curriculum at Darul Hasan Integrated Islamic Junior High School is carried out in accordance with the guidelines provided by the Integrated Islamic School Network. Fortunately, so far, the implementation of the JSIT curriculum at Darul Hasan Integrated Islamic Junior High School has not encountered any significant obstacles.